The jazz divas an analysis of the musical careers of six New Brighton vocalists,The jazz divas : a critical analysis of the life histories and careers and musical careers of six female jazz vocalists in New Brighton, Port Elizabeth from the 1950's to present - Butete, Netsayi (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2012)
There has been insufficient academic research on the music of the Eastern Cape in general and Port Elizabeth and New Brighton in particular. This study, as part of the International Library of African Music (ILAM)lRed Location Museum Music History Project (ILAMIRLMHP) - an oral history intervention to save the music history of New Brighton from extinction through research and documentation of the memories of veteran musicians - is focused on jazz vocalists. The primary objective of my study is to investigate, critically analyze, interpret and document the career experiences of six New Brighton jazz vocalists in the context of performing in the Port Elizabeth music industry during the apartheid and the post-apartheid eras. The secondary objectives are to stimulate research interests in music students and ethnomusicologists to pursue research on the music of Port Elizabeth and the Eastern Cape and to inspire and motivate the vocalists to continue making music with renewed zeal. A qualitative research paradigm informed the field research necessary for this study. The fieldwork paved the way for an eclectic framework of analysis grounded in Pierre Bourdieu's notions of habitus, field and capital, examining the impact of the context on the vocalists' habitus which influenced how they viewed and interpreted their past and current experiences in the performance field. Data obtained through extensive interviewing of New Brighton's contemporary female vocalists and their male counterparts revealed that they have no opportunity to make commercial recordings. The musicians have to migrate to Johannesburg to have successful music careers, although personality politics, greed and lack of professionalism also work against the musicians' success. The data shows that New Brighton musicians, both male and female, do not have enough performance opportunities and there are fewer chances to tour now than there were from the 1960s through the 1980s. As in the apartheid era, female vocalists are still discriminated against in terms of pay, and men discriminate in how they pay other male musicians. Analysis of the vocalists' jazz compositions revealed that their song lyrics depict a bona fide urban African culture and reflect the emotional needs of the society in which they live.
Keywords: Jazz musicians -- Research -- South Africa -- Port Elizabeth; Ethnomusicology -- Research -- South Africa; Sex discrimination against women -- South Africa; Sex discrimination in employment -- South Africa; Apartheid -- South Africa